新加坡中国新移民的网络世界 ：身份认同研究 = Internet world of new Chinese immigrants in Singapore : a study of identity - 黄志豪 Huang, Zhihao (2009)
以各自的身份上网，新加坡中国新移民无论是在部落格，讨论区或是组织性的网站都留下了自己的看法及论点。在虚拟的网络世界，新移民所表现的看法，论点及见解无疑皆有感而发。这些情感也就是发表者对于自己身份认同所释放的线索。身份认同是双方面的；自己对于本身的认同，也存在着外界所给予的认同。身份认同可单一或多重，例如经济认同，国家认同及文化认同。以中国新移民在部落格、讨论区、组织网站所发表的意见及看法为切入点，分析及了解新加坡新移民在网络世界里的思维，心态及想法，从而推论出其身份认同感。Using various identities on the web, new Chinese immigrants have voiced their opinions on respective blogs, forums and organizational websites. In the virtual realm, what they voiced out are usually truthful opinions of their own. Such thoughts and opinions, when voiced out, are usually clues to what each individual feels or perceives of their own identity. Identity is what an individual perceives himself, and what the outside world perceives about him. An identity can be singular or multiple, such as in the forms of economic identity, national identity and cultural identity. Using the new Chinese immigrants’ opinions and thoughts on their blogs, forums and organizational websites as a focal point, this thesis serves to analyze and understand the thoughts, attitudes and opinions of new Chinese immigrants, and hence, examine their perceived identities.